Anallisis Perilaku Pencarian Informasi pada Mahasiswa Jurusan Sosiologi Agama UINSU - Fitriyani Lubis; Halimah Tusadiah; Nursawiyah Nursawiyah; Franindya Purwaningtyas (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The reason someone seeks and carries out the process of searching for informaltion can vary from one person to another. In general, students majoring in the Sociology of Relligion at the University of Indonesia seek informaltion in the library because to meet their information needs, namely in the form of assignments given by the leturer. The research method used in this study is a qualitative descriptive research approach. Based on the results of this study it can be concluded that the pattern of information-seeking behavior owned by each student of the Sociology of Religion UINSU is a starting, verifying, networking element, browsing, extracting, accessing, monitoring and managing information.Kelywords: analysis, behavior, information